1985
DOI: 10.1128/iai.49.2.265-269.1985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemotactins released by Staphylococcus aureus and Pseudomonas aeruginosa on the murine respiratory tract

Abstract: Staphylococcus aureus, the Pseudomonas aeruginosa temperature-sensitive (ts) mutant A/10/25, and the P. aeruginosa parental wild type were aerosolized to CS-deficient mice, and the total number of polymorphonuclear leukocytes (PMN) recovered by lung lavage was determined 4 h after aerosol exposure. S. aureus induced a slight but significant recruitment of PMN, as compared with the effect of a saline aerosol. Both wild-type P. aeruginosa and the ts mutant induced a significant PMN recruitment of a magnitude ca.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…The present study confirmed that this was the case. Competitive binding with anti-aGM1 antibodies reduces bacterial adherence to regenerating cell cultures from cystic fibrosis patients [23], indicating that the glycolipid is a major ligand for pilin protein, though the present study suggests that some cell lines (although expressing aGM1 epitopes) may have other mechanisms for interacting with the Type-IV pilus structure. As such, the role of the aGM1 host cell-surface moiety as a receptor for P. aeruginosa remains controversial, although it was shown that Type-IV pili are important in mediating attachment to cell lines derived from different parts of the human respiratory tract, as well as to rat and mouse respiratory tract epithelial cells, suggesting that these cell lines may be useful models for studying cross-species binding interactions with P. aeruginosa.…”
Section: Cell Linecontrasting
confidence: 52%
See 1 more Smart Citation
“…The present study confirmed that this was the case. Competitive binding with anti-aGM1 antibodies reduces bacterial adherence to regenerating cell cultures from cystic fibrosis patients [23], indicating that the glycolipid is a major ligand for pilin protein, though the present study suggests that some cell lines (although expressing aGM1 epitopes) may have other mechanisms for interacting with the Type-IV pilus structure. As such, the role of the aGM1 host cell-surface moiety as a receptor for P. aeruginosa remains controversial, although it was shown that Type-IV pili are important in mediating attachment to cell lines derived from different parts of the human respiratory tract, as well as to rat and mouse respiratory tract epithelial cells, suggesting that these cell lines may be useful models for studying cross-species binding interactions with P. aeruginosa.…”
Section: Cell Linecontrasting
confidence: 52%
“…The results of the present study indicate that a significant proportion of P. aeruginosa pilA À bind to respiratory epithelium from human, rat and mouse sources, and although this does confirm that the Type-IV pilus structure of P. aeruginosa PAK is the major epithelial cell adhesin [20], the results also confirm that it is only one of numerous structures which mediate attachment of this species of bacteria to the surface of epithelial cells [20]. aGM1 ligands have been reported to mediate the association of P. aeruginosa with respiratory tract cells [19,22,23]. The A549, L-2 and C57 cell lines were all found to bind anti-aGM1 antibodies, the order of binding being; A549 < L-2 < C57, but pre-treatment of the cell lines with P. aeruginosa PAK resulted in a significant reduction in subsequent binding of the anti-aGM1 antibody in A549 cells only.…”
Section: Cell Linementioning
confidence: 84%
“…Our demonstration of the bacterial speciesdependent nature of the eicosanoid profile produced during the interaction of P. aeruginosa and S. aureus with alveolar macrophages is potentially significant with regard to observed differences between the patbophysiological effects of these organisms. For instance, in a mouse model of pneumonia, bronchial challenge with P. aeruginosa has been found to elicit a greater alveolar influx of neutrophils than challenge with S. aureus (18).…”
Section: Discussionmentioning
confidence: 99%
“…(PMNL) has been recognized as one of the most important antibacterial mechanisms of the lung [2]. The extent to which alveolar macrophages and PMNL participate in the early lung clearance of bacteria, however, remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is a tenet of vaccine research that live microbial vaccines usually induce more durable and protective immune responses than killed vaccines [8]. Stimulation of mucosal immunity provides protection against infection with pathogens that normally enter the body through the upper respiratory and oral tracts [2,9]. The present study was aimed at investigating which are the effector mechanisms of lung immunity that are involved in host defense against S. aureus after immunization with live-attenuated S. aureus [10].…”
Section: Introductionmentioning
confidence: 99%